Re-visiting the Easterlin hypothesis: US fertility 1968 - 2010 - Diane Macunovich (Institute for the Study of Labor (IZA), 2011)
This study tests the effect of relative income - younger people's earning potential relative to their aspirations, as approximated by older families' income - on two measures of fertility: the proportion of women with an own child under one year of age, and the proportion of women with at least one own child under eighteen. The results are highly supportive of the Easterlin relative income hypothesis, finding a dominant negative effect of older family income that extends due to postponement effects even into groups 11-15 years out of school. Increases in older family income are found to account for 42% of the decline in the proportion of women with a newborn, and 37% of the decline in the proportion with at least one own child, among women 0-5 years out of school. In addition, the study finds a strong but changing effect of the female wage: positive among women 0-5 years out of school, although slowly declining over time, but negative among the older women with a dominant positive time trend that has produced a positive effect in the last decade. It is hypothesized that the observed pattern of increases in fertility among women with higher levels of education over the last decade has been a function of this emerging positive effect of the female wage, among older more educated women.
urn:nbn:de:101:1-201108093151
Keywords: J13; 330; fertility; relative income; relative cohort size; Easterlin hypothesis